PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN - Benedictus Dimas Widyatama; Agustinus Santosa Adi Wibowo (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to analyze the effect of corporate governance mechanisms on financial performance. The population in this study are all manufacturing companies listed on the Stock  Exchange  in  2011  until  2013.  The  sampling  method  used  in  this  study  was  purposive sampling method.The total number of samples in this study were 90 research samples. This study used multiple linear regression as analysis instrument. Before doing the regression test, it’s examined by using classical assumption test. The results of this study indicate the size of the audit committee, managerial ownership, and the number of audit committee meetings do not affect the financial performance. While the number of board meetings significant negative effect. From this study only board size and independence of the board of commissioners that significant positive effect on financial performance.